Essays on forestry economics - Rosa, Renato (2021)
In this dissertation, optimal forest management and land use allocation are analyzed when biodiversity and carbon sequestration benefits are introduced into the forest agent problem. In particular, forest carbon sequestration is studied under two different scenarios: the first considers the problem of the small private owner, while the second focuses on the management of a public forest, when timber and land prices are endogenously determined. In the first paper, based on a multiple rotation model à la Faustmann in which optimal land use conversion time is endogenous, we discuss the implementation of the optimal solution from the small private owner’s perspective . Given the important role of the “permanence” issue in the context of the United Nations Framework Convention on Climate Change, two different accounting methods (the Carbon Flow and the Ton-Year Crediting) with constant and rising carbon prices are analyzed. It is shown that the use of different carbon methods strongly impacts optimal rotations and forest profitability, implying that short and long run timber supplies are also affected by the carbon accounting method choice. Moreover, the consideration of carbon stored in long-lived wood products affects the optimal land use conversion time when carbon prices are increasing. An application to the portuguese Eucalyptus forest confirms these results. In particular, as immediate land use conversion is optimal for most cases considered, the idea that forests may provide the economic incentives needed to change land-use decisions, buying time for the development and deployment of low carbon-based technological innovations, is reinforced. The second paper adresses the question of optimal timber management when carbon benefits are introduced into a framework where both the price of timber and the price of land are endogenously determined. Building upon the multi vintage forest model developed by Salo and Tahvonen, the paper analyzes the problem of carbon sequestration under a forest sector scope. To compare forest carbon sequestration with avoided emissions, three different carbon accounting methods are considered: the carbon flow regime, the ton-year crediting and the average storage, where the carbon flow is the first-best solution. We compare the results obtained in each case with those without carbon sequestration, as well as the performances of the ton-year and the average storage with respect to the first-best solution on optimal land allocation between forestry and alternative uses, total carbon sequestered, timber production and social welfare, for different values of the most relevant parameters. In general, internalizing carbon sequestration benefits increases the optimal amount of land allocated to forest, and has implications to the optimal forest management. The induced impact in the timber market during the transition period depends upon the carbon accounting method generating interesting insights from the perspective of the implementation of the first-best solution. A full proof of long-run optimality of steady state forest is provided. The theoretical results are discussed based on numerical simulations that illustrate the setup’s potential. The recent recognition of the existence of possible conflicts between carbon sequestration policies and biodiversity has once more put biodiversitiy in the centre of the forestry literature debate While a complete assessment of the interactions between carbon sequestration policies and biodiversity conservation is still needed, there are previous questions in the biodivesity literature that remains to be addressed, namely, in what concerns the forest sector scope. To this end, in the third essay, biodiversity considerations are introduced into a multiple species, multi-vintage forest sector model with endogenously determined timber prices and land use allocation. Following recent ecological literature, biodiversity is modeled focusing on structural diversity, i.e, age classes and species distribution. We show that transition dynamics are strongly affected when biodiversity is introduced, contaminating both timber and land markets. Moreover, different ecological forest structures have distinct impacts on optimal land use distribution, therefore, affecting also timber prices. Finally, we observe major changes in optimal timber management. In fact, even after a long period of adjustment, optimal deviations from Faustmann’s rotation combined with changes in land use allocation still occur. The fourth essay extends the multi vintage forest model developed in the second by introducing net carbon sequestration benefits in a multiple species context. Based on the carbon flow accounting method, a full proof of long run optimality of steady state forest is provided. Based on sensitivity analysis with respect to the speed of growth, the carbon conversion factor and the amount of carbon that is stored in long-lived wood products among species, we conclude that they impact significantly on the optimal allocation of land to forest. In particular, when the fast growing species is also the one for which a lower fraction of wood is used in long-lived products, it may be optimal to allocate to the slow growing species a larger amount of land when compared to the case without carbon. Numerical simulations are performed, illustrating and confirming the results obtained.